2019
DOI: 10.1080/1828051x.2018.1549513
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carcase conformation and fat cover scores (EUROP system) on the quality of meat from young bulls

Abstract: The EUROP classification system includes only a small number of indicators to characterise beef carcases, none of which directly describes meat quality. Therefore, beef producers show limited interest in improving meat quality parameters. The aim of this study was to evaluate whether conformation and fat cover, as assessed in the EUROP classification system, can be reliable descriptors of the qualitative characteristics of beef carcases and meat quality. A total of 198 carcases of young bulls were analysed. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Consistent with the findings of this investigation, marbling in the AMR group was substantially higher than that of the other two groups (P < 0.05), and AMR powder promoted the homogeneous distribution of intermuscular fat in ASH lambs. Existing research indicates that there are fewer fat deposits between muscles, which are adverse to meat quality (Nogalski et al, 2019). The results demonstrated that feeding AMR powder improved meat quality, while giving DGS had no negative influence on meat quality.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with the findings of this investigation, marbling in the AMR group was substantially higher than that of the other two groups (P < 0.05), and AMR powder promoted the homogeneous distribution of intermuscular fat in ASH lambs. Existing research indicates that there are fewer fat deposits between muscles, which are adverse to meat quality (Nogalski et al, 2019). The results demonstrated that feeding AMR powder improved meat quality, while giving DGS had no negative influence on meat quality.…”
Section: Discussionmentioning
confidence: 88%